FACTORS ASSOCIATED WITH DEVELOPMENT OF TYPHOID FEVER AT KAZIWIZIWI COAL MINING AREA IN RUMPHI DISTRICT, MALAWI: A Retrospective Case Control Study - Mbakaya, Balwani Chingatichifwe; Mukora-Mutseyekwa, Fadzai; Chideme-Munodawafa, Auxillia; Mwale, Charles Masulani; Mnyenyembe, Letcher Mwenegamba (European Scientific Journal, ESJ, 2015)
Introduction: Kaziwiziwi is a coal mine situated in the eastern and mountainous area, 60km from Rumphi Boma in Malawi. The mine has a population of about 350 workers. Outbreak of typhoid occurred from 21st May to 15th June, 2012, at the mining area. Therefore the investigation of the outbreak was instituted to establish risk factors associated with the development of typhoid. Methodology: An unmatched 1:1 case-control study design was used to establish the relationships between the risk factors and the development of typhoid. Anyone who suffered from typhoid in the month of May and June 2012 and living within the area was regarded as a case. A control was any participant who had the same characteristics like the cases except for the contraction of typhoid during the same period, in the area. An interviewer administered questionnaire was used to collect data. Results: A total of 50 cases and 50 controls consented to participate in the study. Risk factors such as use of untreated water from a nearby river, drinking locally prepared thobwa (sweet mild beer) and not having a facility for hand washing after toilet use were associated with contracting typhoid with OR [2.7(95%CI 1.2, 6.3) p=0.0176], [OR, 1.8(95% CI 0.8, 3.96)p=0.1127] and [OR, 2.6(CI 1.1,6.1) p=0.0236] respectively. Discussion and Conclusion: Like some previous studies, use of water from the river and not washing hands after using toilet were the main risk factors associated with contracting typhoid. The water from the river needs to be treated before use and health education campaigns with targeted health promotion messaging should be conducted in the area to avoid recurrence of the outbreak.